Criminal Liability for Criminal Defendants Participating in Unlicensed Gold Mining - Fitriati; Tamsir (Master of Law Program, Ekasakti University, 2023)
Broadly speaking, mining business activities carried out without a permit can be subject to criminal charges as well as the criminal act of participating in gold mining activities without a permit has fulfilled the elements of a criminal act and can be subject to criminal sanctions as stated in the criminal provisions of Article 158 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining juncto Article 55 paragraph (1) 1 of the Criminal Code and Criminal Procedure Code as a single indictment, as a form of criminal liability. While the consequences of illegal gold mining cause so much damage that occurs both on land and in river flows, caused by the rampant illegal gold mining activities (dompeng) along the river flow. The specification of this study is that it is descriptive analytical research. The approach method used is normative juridical supported by empirical juridical approach. The data used is the secondary data inputted. The data obtained are analyzed qualitatively and presented in an analytical descriptive manner. Based on research and discussion, it can be seen that: First, criminal liability for criminal defendants participating in unlicensed gold mining based on the decisions of the Kuantan Bay District Court Number: 98/Pid.B/LH/2021 and Number: 99/Pid.B/LH/2021, namely imprisonment and fines for the defendant, because they have The fulfillment of the conditions that the defendant can be held criminally responsible, the defendant is sentenced to a criminal sentence in the form of imprisonment for 1 (one) year and a fine of Rp. 800,000,000.00 (eight hundred million rupiah) provided that if the fine is not paid it is replaced by imprisonment for 3 (three) months. Second, the judge's consideration of the decisions of the Kuantan Bay District Court Number: 98/Pid.B/LH/2021 and Number 99/Pid.B /LH/2021 in the crime of unlicensed gold mining, namely the Judge in handing down decisions will consider juridical and non-juridical matters, but in general, Judges in sentencing perpetrators of unlicensed gold mining crimes are more likely to use juridical considerations than non-juridical ones, as referred to in the decision of the Kuantan Bay District Court Number 98/Pid.B/LH/2021 and Number: 99/Pid.B/LH/2021 in the criminal act of unlicensed gold mining.